1978
DOI: 10.1093/geronj/33.5.737
|View full text |Cite
|
Sign up to set email alerts
|

Age Changes, Cohort Differences, and Cultural Change on the Guilford-Zimmerman Temperament Survey

Abstract: The relation between adult age and temperament was investigated using the Guilford-Zimmerman Temperament Survey. Between the years 1958 and 1974, the GZTS was administered to 915 men from 17 to 98 years of age in the Baltimore Longitudinal Study. Repeated measures were obtained for 336 men approximately 7 years after initial testing. Each GZTS scale was analyzed cross-sectionally and longitudinally. Sequential analyses of independent samples were also carried out in an attempt to separate the effects of matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 0 publications
3
36
1
Order By: Relevance
“…Repeated measures analyses of the GZTS in BLSA men reported by Douglas and Arenberg (1978) showed declines in five of the ten scales, but a consideration of cross-sectional and other analyses led them to conclude that only two scales-General Activity and Masculinity-showed true maturational decline. Similarly, Costa and McCrae (1988b) found statistically significant changes in 9 of the 23 scales of the NEO-PI when scores from 398 Augmented BLSA men and women were examined over a 6-year period.…”
Section: Mean Level Stability or Change: Seeking Developmental Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated measures analyses of the GZTS in BLSA men reported by Douglas and Arenberg (1978) showed declines in five of the ten scales, but a consideration of cross-sectional and other analyses led them to conclude that only two scales-General Activity and Masculinity-showed true maturational decline. Similarly, Costa and McCrae (1988b) found statistically significant changes in 9 of the 23 scales of the NEO-PI when scores from 398 Augmented BLSA men and women were examined over a 6-year period.…”
Section: Mean Level Stability or Change: Seeking Developmental Trendsmentioning
confidence: 99%
“…Thus, researchers may wish to estimate the stability of individual differences on a trait measure (e.g. Costa, McCrae and Arenberg, 1980), or they may wish to separate maturational changes from generational differences (Douglas and Arenberg, 1978). Longitudinal studies can provide crucial evidence on the causal ordering of variables that may be confounded in retrospective reports (Costa, Fleg, McCrae and Lakatta, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…While we think most often of the physiological aspects of aging (structural, cellular, morphological), changes occur in psychological and sociological aspects of function as well [8,9]. Some have suggested that personality changes with aging [10,11] as individuals interact with environmental events [12,13]. Cognitive changes with aging have been reported [14].…”
Section: What Happens When We Age?mentioning
confidence: 99%
“…Scales such as the Maudsley Personality Inventory (Sugiyama, 1984), the Marke Temperament Schedule (Nilsson & Persson, 1984), the Hand Test (Panek et al, 1976) and the Guilford-Zimmerman Temperament Survey (Douglas & Arenberg, 1978) provide profiles of personality on the basis of univariate conceptualizations or theories with limited ranges of factors or scales. However, the design of the present study was derived from the incomplete and piecemeal nature of these studies in an effort to relate depressive symptom complexes to multivariate measures of personality.…”
Section: Rationalementioning
confidence: 99%